1992
DOI: 10.1002/hep.1840160513
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide inhibits the meal-induced increases in the portal venous pressure of cirrhotic patients with portal hypertension: A double-blind, placebo-controlled study

Abstract: The aim of this study was to determine the effects of the long-acting somatostatin analog, octreotide, on portal venous pressure and collateral blood flow in cirrhotic patients with portal hypertension during fasting and postprandial states. In a double-blind, placebo-controlled study, we investigated the effects of octreotide on the hepatic venous pressures and azygos blood flow of 21 patients before and after a standard liquid meal containing 40 gm of protein in 250 ml. Octreotide significantly reduced azygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 33 publications
1
39
0
1
Order By: Relevance
“…The exact mechanisms of the hemodynamic changes in response to octreotide are partly unknown, 1 and only a transient or no effect on hepatic venous pressure gradient (HVPG) has been demonstrated. [2][3][4][5][6] Lately, a marked increase of lower esophageal sphincter pressure has been described in response to intravenous octreotide in portal hypertensive patients in addition to a sustained suppression of postprandial splanchnic hyperemia. 3,[7][8][9] These effects coincide with a reduction of plasma glucagon, 8,9 and this mechanism has been thought to be responsible for the suppression of splanchnic hyperemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanisms of the hemodynamic changes in response to octreotide are partly unknown, 1 and only a transient or no effect on hepatic venous pressure gradient (HVPG) has been demonstrated. [2][3][4][5][6] Lately, a marked increase of lower esophageal sphincter pressure has been described in response to intravenous octreotide in portal hypertensive patients in addition to a sustained suppression of postprandial splanchnic hyperemia. 3,[7][8][9] These effects coincide with a reduction of plasma glucagon, 8,9 and this mechanism has been thought to be responsible for the suppression of splanchnic hyperemia.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] Lately, a marked increase of lower esophageal sphincter pressure has been described in response to intravenous octreotide in portal hypertensive patients in addition to a sustained suppression of postprandial splanchnic hyperemia. 3,[7][8][9] These effects coincide with a reduction of plasma glucagon, 8,9 and this mechanism has been thought to be responsible for the suppression of splanchnic hyperemia. However, a recent study indicates that octreotide has direct vasoconstrictive effects in cirrhotic patients unrelated to the effects on glucagon and other vasoactive hormones and neuropeptides 10 that may seriously influence renal function in these patients.…”
mentioning
confidence: 99%
“…18,19 It has also been shown that octreotide blunts this postprandial increase both in normal subjects 20,21 and cirrhotic patients. [22][23][24] Recently, a new long-acting somatostatin analog, lanreotide, has been developed. 25 The hemodynamic effects of this peptide in humans are yet unknown.…”
mentioning
confidence: 99%
“…In the light of our results, we can hypothesize that other physiologic situations known to transiently increase portal pressure and/or AzBF, such as moderate physical exercise 11,12 or meals, [13][14][15][16][17][18][19][20] may cause significant increases in variceal pressure. It is of interest to note that propranolol therapy has been shown to prevent the changes in HVPG associated with moderate exercise.…”
Section: Discussionmentioning
confidence: 95%